Predicting the Rise of EU Right-Wing Populism in Response to Unbalanced Immigration - Boris Podobnik; Marko Jusup; Dejan Kovac; H. E. Stanley (Complexity)
Among the central tenets of globalization is the free migration of labor. Although much has been written about the benefits of globalization, little is known about its limitations and how antiglobalist sentiment can be strongly affected by high levels of immigration. Analyzing poll data from a group of EU countries affected by the recent migrant crisis, we find that over the last three years the percentage of right-wing (RW) populist voters in a given country depends on the prevalence of immigrants in this country’s population and the total immigration inflow into the entire EU. The latter is likely due to the perception that the EU functions as a supranational state in which a lack of inner borders means that “someone else’s problem” can easily become “my problem.” We find that the increase in the percentage of RW voters substantially surpasses the percentage of immigration inflow, implying that if this process continues, ongoing democratic processes will cause RW populism to prevail and globalization to rapidly decrease. We locate tipping points between the fraction of immigrants and the rise of RW populism, and we model our empirical findings using a complex network framework in which the success of globalization rests on a balance between immigration and immigrant integration.